Avaliação do emprego de diferentes medidas hemostáticas no controle do sangramento pós--exodontia de pacientes sob terapia anticoagulante - Batista, Saulo Hilton Botelho (2010)
The therapeutic use of Varfarin, the most common oral anticoagulant it is indicated in many cases, including the atrial fibrillation, cardiac valvular prostheses and venous trombolic disease. Many discussions still exist related to the suspension or not before tooth extraction. People who are for it’s suspension agree that it may increase the risk of hemorrhage, however the ones who prefer to maintain it’s use refer the high risk of tromboembolism. Due to the controversy related to the cronic use of oral anticoagulant before tooth extraction and what to use to control bleeding after extraction, we decided to perform a one center randomized clinical trial study to compare the effectiveness of the hemostasis using soaked gauze with tranexamic acid at 4,8% and plain gauze and the use of collagen sponge (Hemospon®), using it inside the tooth socket after extraction. The sample was made of 84 surgical procedures performed in 38 patients who were under anticoagulant treatment and who needed at least one tooth extraction. The trial was divided in three groups regarding the method used to reach hemostasis after tooth extraction. In group I we used compression with soaked gauze with tranexamic acid at 4,8%; in group II we used collagen sponge (Hemospon®) inside the socket while in group III we compressed the socket with dry gauze for 8 minutes. There were two cases of post surgical bleeding, being one from group I and one from group II. The data collected was evaluated thru SPSS 1.5 (Statistic Package of Social Science) program. All the statistical analysis performed were considered significantly when p was less than 5%. We used the Qui square X2 Test, Fisher Exact Test e Analysis of Variance (ANOVA) to verify the variables of the data. There was no statistically significant difference between the groups, related to bleeding (p>0,05). The compression with dry gauze and suture, compression with soaked gauze with trenaxamic acid at 4.8% and suture and the use of collagen sponge (Hemospon®) in the tooth socket hold with suture showed similar efficacy to the control of post extraction bleeding in patients who are under anticoagulant treatment.